Pengaruh Store Atmosphere, Kualitas Pelayanan dan Customer Experience Terhadap Kepuasan Konsumen di Bhineka Muda Merdeka Denpasar - Ni Putu Shinta Vishuda Yoga Sasmitha; I Wayan Ruspendi Junaedi; I Gede Agus Mertayasa (Pusat Riset dan Inovasi Nasional, 2022)
In order to find out indications of the influence of store atmosphere, service quality, and customer experience on consumer satisfaction at Bhineka Muda Merdeka, a study using a population, namely all consumers from Bhineka Muda Merdeka Denpasar, took a sample of 120 people. Based on these results, it can be concluded that the indication of store atmosphere has a positive and significant impact on customer satisfaction with the results of t-count 3,425 > t-table value 1,7 and a significance value of 0,001 <0,05. Another indication is that the quality of service has a positive and significant impact on consumer satisfaction, with the results of t-count 2,699 > t-table value 1,7 and a significance value of 0,008 <0,05. The last indication is that customer experience has a positive and significant impact on consumer satisfaction, with the results of t-count 2,910 > t-table value 1,7 and a significance value of 0,004 <0,05. Broadly speaking, there are indications simultaneously between store atmosphere, service quality, and customer experience on customer satisfaction of 34,9%.